Measurement of the top quark forward-backward production asymmetry and its dependence on event kinematic properties - Collaboration, CDF; Aaltonen, T; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2012)
We present new measurements of the inclusive forward-backward ttbar production asymmetry, AFB, and its dependence on several properties of the ttbar system. The measurements are performed with the full Tevatron data set recorded with the CDF II detector during ppbar collisions at sqrt(s) = 1.96 TeV, corresponding to an integrated luminosity of 9.4 fb^(-1). We measure the asymmetry using the rapidity difference Delta-y=y_(t)-y_(tbar). Parton-level results are derived, yielding an inclusive asymmetry of 0.164+/-0.047 (stat + syst). We observe a linear dependence of AFB on the top-quark pair mass M(ttbar) and the rapidity difference |Delta-y| at detector and parton levels. Assuming the standard model, the probabilities to observe the measured values or larger for the detector-level dependencies are 7.4*10^(-3) and 2.2*10^(-3) for M(ttbar) and |Delta-y| respectively. Lastly, we study the dependence of the asymmetry on the transverse momentum of the ttbar system at the detector level. These results are consistent with previous lower-precision measurements and provide additional quantification of the functional dependencies of the asymmetry.